Nutritional indicators of adverse pregnancy outcomes and mother-to-child transmission of HIV among HIV-infected women - Mehta, Saurabh (2008)
BACKGROUND: Poor nutrition may be associated with mother-to-child transmission (MTCT) of HIV and other adverse pregnancy outcomes. OBJECTIVE: The objective was to examine the relation of nutritional indicators with adverse pregnancy outcomes among HIV-infected women in Tanzania, Zambia, and Malawi. DESIGN: Body mass index (BMI; in kg/m(2)) and hemoglobin concentrations at enrollment and weight change during pregnancy were prospectively related to fetal loss, neonatal death, low birth weight, preterm birth, and MTCT of HIV. RESULTS: In a multivariate analysis, having a BMI < 21.8 was significantly associated with preterm birth [odds ratio (OR): 1.82; 95% CI: 1.34, 2.46] and low birth weight (OR: 2.09; 95% CI: 1.41, 3.08). A U-shaped relation between weight change during pregnancy and preterm birth was observed. Severe anemia was significantly associated with fetal loss or stillbirth (OR: 3.67; 95% CI: 1.16, 11.66), preterm birth (OR: 2.08; 95% CI: 1.39, 3.10), low birth weight (OR: 1.76; 95% CI: 1.07, 2.90), and MTCT of HIV by the time of birth (OR: 2.26; 95% CI: 1.18, 4.34) and by 4−6 wk among those negative at birth (OR: 2.33; 95% CI: 1.15, 4.73). CONCLUSIONS: Anemia, poor weight gain during pregnancy, and low BMI in HIV-infected pregnant women are associated with increased risks of adverse infant outcomes and MTCT of HIV. Interventions that reduce the risk of wasting or anemia during pregnancy should be evaluated to determine their possible effect on the incidence of adverse pregnancy outcomes and MTCT of HIV.